My Early Life : A Roving Commission - Churchill, Winston, 1874-1965 (London Thornton Butterworth Limited, 1930)
Written when he was barely thirty, Winston Churchill describes his early years.
Include Index
Keywords: Great Britain. Army -- Armed Forces--Military life